Amphorae from the Kops Plateau (Nijmegen) : trade and supply to the lower-Rhineland from the Augustan period to AD 69/70 - Carreras Monfort, César,; Berg, Joost van den, (Archaeopress Roman archaeology ;, 2017)
The amphorae from Kops Plateau represent a singular example of Roman military supply in northern Europe at a very early date. Their analysis sheds light on trading routes in the Atlantic regions, and from Gaul to Germany.